119 In Vivo EPID Dosimetry: Time workload analysis. (December 2018) - Giancaterino, S.; Grimaldi, L.; Berlinghieri, S.; Castrezzati, E.; Di Santo, S.; Morandini, V.; Spiazzi, L.; Frata, P.
Abstract: Purpose: In Vivo EPID dosimetry, is a time-consuming procedure. This paper reports a time workload analysis of SOFTDISO software (SW) (Best Medical Italy) obtained in our center. Methods: the time workload analysis was subdivided into two phases: the first regard pre-clinical mounting in particular the creation of communication DICOM nodes ( t links ), the SW commissioning time ( t commissioning ) and the radiology technician training time ( t training ) ; the second refer to clinical routine. This last phase was divided in four steps: single patient's loading times, t load, (import patient from TPS to SW, t TPS-SW, and from TPS to EPID management device, t TPS - EPID ) ; single patient's daily synchronization time on SW, t synchro ; single patient's setting time, t set-up ; time of troubles, t troubles . In our center the TPS was Pinnacle 9.10 (Philips) and EPID device was IViewGT (Elekta). Results: The pre-clinical phase required about three weeks where a multi-disciplinary team (medical physicist, product specialist and system administrator) has worked to interface all devices, the medical physicist has performed the SW commissioning measure and along with the product specialist they trained the staff. For a single patient by the clinical times shows inTable 1 we can calculate the daily time, t daily, equal to (240 ± 135) s and the insertion time, t load, equal to (180 ± 30) s. This time analysis was performed overall 30 patient. The daily workload was estimated from 10 of 20 patients treated per day who undergo to in vivo dosimetry checks and was equal to 45 min. Conclusions: After a month a medium sized radiotherapy center gets these results with a dedicated medical physicist and a radiology technician. Additional clinical time is required to discuss the out of tolerance value provided by the SW. This time was estimated in 1 h per week.